2019
DOI: 10.1002/ajoc.201900641
|View full text |Cite
|
Sign up to set email alerts
|

Iron‐Catalyzed Chemoselective C−N Coupling Reaction: A Protecting‐Group‐Free Amination of Aryl Halides Bearing Amino or Hydroxy Groups

Abstract: A chemoselective C−N coupling (Buchwald‐Hartwig‐type) reaction of diarylamines with aryl halides bearing non‐protected amino or hydroxy groups proceeds in the presence of a simple iron catalyst. Upon treatment with Grignard reagents, various diarylamines can be cross‐coupled with halocarbazoles, haloindoles, haloanilines, and halophenols to afford the corresponding triarylamines, without the undesired dimerization or oligomerization of the starting aryl halides. DFT studies on the dimeric iron amide intermedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…To address this, it was necessary to expand the ADs of the yield prediction models and design new experimental conditions. Therefore, after the two samples in Table were added to the initial 73 samples, we collected experimental datasets described in scientific papers on BHCC and SMCC reactions and added them to our dataset to increase the scope of the catalyst structures and experimental conditions. The added experimental datasets included catalysts with transition metals such as Ni, Pd, Cu, Fe, and so forth and ligands that are different from our dataset.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To address this, it was necessary to expand the ADs of the yield prediction models and design new experimental conditions. Therefore, after the two samples in Table were added to the initial 73 samples, we collected experimental datasets described in scientific papers on BHCC and SMCC reactions and added them to our dataset to increase the scope of the catalyst structures and experimental conditions. The added experimental datasets included catalysts with transition metals such as Ni, Pd, Cu, Fe, and so forth and ligands that are different from our dataset.…”
Section: Resultsmentioning
confidence: 99%
“…Since we focused on the combination of catalysts and ligands, we used the same experimental conditions for the solvent, base, reaction time, and reaction temperature as in our dataset. For the experimental catalysts and ligands, 33 catalysts from our dataset and 23 from collected papers were employed, and 52,000 compounds from the Namiki Shoji database were used as ligands.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the same group [24] reported another iron-catalyzed chemoselective CÀ N coupling reaction of diarylamines with aryl halides bearing a free amino group (Scheme 6). Preliminary DFT studies indicated that the reaction involved a dimeric-Fe active species, and the chemoselectivity was controlled by kinetics.…”
Section: Iron-catalyzed Csp 2 -N Bond Formationmentioning
confidence: 99%
“…The C–N cross‐couplings executed by transition‐metal catalysts immersed eloquent part in the construction of a variety of commercially potent organic molecules. [ 28–30 ] Among the C–N coupled products, N ‐arylimidazoles and N ‐arylbenzimidazoles draw considerable attention due to their widespread use in organocatalysis, ionic liquids, and pharmaceutical, biological, and material interest. [ 29,31–33 ] Common strategies to access the arylated amines include (i) the activation of aryl halide/ethers/esters toward aromatic nucleophilic substitution (S N Ar) using amines, [ 34–36 ] (ii) Ullmann/Buchwald–Hartwig coupling of aryl halides and amines, [ 37–40 ] and (iii) Chan–Lam coupling of arylamines and arylboronic acids.…”
Section: Introductionmentioning
confidence: 99%